THE INTERACTION MODEL OF ECONOMIC GROWTH RATE AND COVID-19 SPREAD IN INDONESIA USING THE SIRS MODEL - Khansa Alifa, Naura
The COVID-19 pandemic poses a serious threat to public health and the economy worldwide. This study examines the interaction between economic growth rates and the spread of COVID-19 in Indonesia using the SIRS model method. The analysis includes the identification of equilibrium points and stability analysis to understand the long-term dynamics of these two variables. Economic conditions are measured by GDP, and its development over time is formulated with a logistic model. The results of the study indicate that the spread of COVID-19 has a significant impact on economic growth. The Nonlinear Least Squares method is used to estimate the parameters of the disease transmission rate (????), recovery rate (????), immunity rate (????), the proportion of susceptible individuals quarantined (????1), and the proportion of infected individuals quarantined (????2). The estimated values of the parameters are used to compare the model with actual data at each phase of the COVID-19 spread. A sensitivity analysis of the model parameters is conducted to determine how variations in the model inputs affect the outputs. The author varies the values of the parameters ,????,????,????1, and ,????2 by adding/subtracting 10% of their respective values. As the value of ????, COVID-19 will be more effectively controlled by slowing the transmission rate of the disease. Simulations of the mathematical model provide insights into policy interventions that can be implemented to mitigate the spread of the COVID-19 virus on Indonesia's economy.